Matlab mapping of full field peripheral refraction profile with multifocal contact lenses in myopes - Mitra, K; Ramasubramanian, V (International Journal of Computer Sciences and Engineering, 2025)
Purpose: MFCLs have been a better choice for myopia control followed by Ortho K lenses presumably by inducing a relative peripheral myopia. The study was done in emmetropes and myopes to assess the peripheral refraction (PR) profile at all possible eccentricities to have a better understanding of myopia control with the help of MATLAB. Methods: 5 emmetropes and 18 myopic adults of age 18-30 years with -0.50 to -6.00 D spherical component and less than 1.00 D astigmatism were fitted with commercially available center near multifocal soft contact lenses with low and high add. Center and peripheral refraction were measured under cyclopleigia at all possible eccentricities ranging from 0-180, 90-270, 30-210, 60-240, 120-300, 150-330 under four conditions: baseline (No lens wear); single vision spherical(SVCL); MFCL low add and MFCL high add by using Grand-Seiko WAM 5500 autorefractor with the help of MATLAB programming. Measurements are taken in Single Click Mode and High Speed Mode. Results are interpreted as a change in relative PR profile as refractive power vector components; M, J0 and J45 and analysed using a separate MATLAB program. Results: The results show statistically significant differences (p<0.05) between each condition for means of High speed mode and M value in each meridian. MFH showed a myopic defocus nasally but temporally there was hyperopic defocus. Conclusion: In comparison to high add, center near multifocal low add showed a more myopic periphery both temporally and nasally in young myopes.